Proximate analysis of selected freshwater fish in Kuantan, Pahang - Abdul Halim, Nazirah; Mat Jusoh, Hanapi (International Islamic University Malaysia, 2020)
Introduction: The purpose of this study was to evaluate proximate composition of freshwater fish that are commonly consumed by Malaysians namely Clarius batrachus (Keli), Oreochromis niloticus (Tilapia merah), Pangasius hypophthalmus (Patin) and Channa striata (Haruan). Methods: The proximate composition of moisture, protein, fat and ash were measured according to method described by Association of Official Analytical Chemists (AOAC) 1990 with slight modifications. Data was analyzed using Analysis of Variance (ANOVA), with a significance level used for all tests was at 95% (p<0.05). Results: Our results showed that all four species of fish had the moisture contents between 71.1-81.2% with the lowest seen in C. batrachus. The protein contents were comparable between species ranging from 1.98-3.21%, although the values were significantly lower than those reported in other studies. The fat content was the highest in C. batrachus (10.38%) while the other species had comparable values ranging from 0.33-1.53%. No differences were seen in ash contents between all species with percentage ranging from 0.91-1.11%. Conclusion: The selected freshwater fish contain comparable proximate composition except for C. batrachus that had the lowest moisture and higher fat contents.